High frequency of temperature-sensitive mutations of p53 tumor suppressor in acute myeloid leukemia revealed by functional assay in yeast - Pavlova, Sarka; Mayer, Jiri; Koukalova, Hana; Smardova, Jana (International journal of oncology, 2003)
The tumor suppressor p53 is a transcription factor that participates in control of many cellular functions. All these activities are mediated by direct binding of the p53 tetramer to specific target sequences in promoters of directed genes. Lack of p53 function is often connected with development of cancer, but the frequency of p53 mutations is low in almost all types of leukemia. The aim of this study was to assess the frequency of mutations in the p53 gene in leukocytes of patients with acute myeloid leukemia (AML) using the FASAY functional analysis and to assess the relationship between the presence of p53 mutation and disease outcome. The following observations were made: i) the presence of p53 mutations was detected in 13 of 62 tested AML cases (21%) and in 1 of 4 tested myelodysplastic syndrome (MDS) cases by FASAY; ii) the presence of p53 mutation was shown to be a poor prognostic/predictive factor in AML (p=0.03/0.002); iii) although there is a statistically significant relationship between the presence of p53 mutation and p53 protein accumulation (p=0.05), not all samples having p53 mutation exhibited p53 protein accumulation; iv) five of 13 p53 mutations detected in the leukocytes of AML patients (38.5%) and the mutation detected in the leukocytes of the MDS patient (altogether 6/14-42.9%) were partially inactivating ts mutations. The high frequency of the ts p53 mutations in our study; and a novel modification in performing FASAY, are discussed; v) different ts mutations differ in the level of their temperature sensitivity and in their responsiveness to the cytoprotective drug amifostine.
Keywords: mutace; dospělí; genetické techniky; Tumor Suppressor Protein p53; amifostin; Female; Fungal Proteins; Genes, p53; teplota; Adult; ženské pohlaví; mutační analýza DNA; Amifostine; Adolescent; Time Factors; časové faktory; geny p53; lidé; Yeasts; DNA Mutational Analysis; Mutation; Aged, 80 and over; RNA komplementární; Immunoblotting; prognóza; leukocyty; Temperature; Male; plazmidy; kvasinky; Aged; fungální proteiny; Radiation-Protective Agents; akutní myeloidní leukemie; nádorový supresorový protein p53; Leukocytes; Genetic Techniques; Prognosis; lidé středního věku; senioři nad 80 let; imunoblotting; senioři; mužské pohlaví; Plasmids; RNA, Complementary; Middle Aged; mladiství; Leukemia, Myeloid, Acute; radioprotektivní látky; Humans